Effectiveness and safety of cataract surgery in laminar air flow device versus traditional scrubs: A 1-year non-inferiority pilot study - Artus, Arnaud; Fabro, Filippo; Cochereau, Isabelle; Caputo, Georges; Tadayoni, Ramin; Vignal, Catherine; Galatoire, Olivier; Salviat, Flore; Gatinel, Damien; Panthier, Christophe (Frontiers in Medicine, 2023)
Purpose: To assess the safety of cataract surgery outside an operating theater with the Surgicube®, a mobile laminar airflow (LAF) device. Settings: Single center study at the Rothschild Foundation, Paris, France Design: Retrospective cross-sectional study Methods: All patients operated of cataract at the Surgicube® between February 2020 and February 2021 were included and controlled by a cohort of patients operated of cataract in the traditional theater during the same period. Patients with a postoperative follow-up of less than 1 month were excluded. Data collection was done using the patient's medical record. The primary endpoint was the evaluation of the number of endophthalmitis in the two groups. The secondary judgment criteria were the analysis of the various complications and the Logmar visual acuity at 1 month in the two groups. Conclusion: cataract surgery with the Surgicube® outside a conventional operating room seems to be a valid alternative to conventional scrub.